PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA GURU SMKN 4 KLATEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - ., Sarbin (ADVANCE, 2014)
The aim of this study is investigate the influence of leadership, communication, and job satisfaction to teachers performance of the Government Vocational High School 4 at Klaten. The research is a survey to teacher performance at the Government Vocational High School 4 at Klaten Data have been collected with questionair was processed with, validity and reliability test, the path analysis, t test, F test and test of R2. The t test result show that there is influence of leadership, communication, and job satisfaction to teacher s performance at the Government Vocational High School 4 at Klaten. The F test result show that there is influence of leadership, communication, and job satisfaction to teacher performance the Government Vocational High School 4 at Klaten simultaneously. From path analysis shows that leadership has a less influence to performance than across job satisfaction, so that communication. It means that job satisfaction canât be as an intervening variable because the coefficient is smaller than coefficient as direct influence. From test of R2 shows that the independent variable can explain performance about 80 % and 20% can be explained by other variables: commitment, ability. Keyword: leadership, communication, job satisfaction, performance.